Cameroon : Report on Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2001)
The principal standard against which the transparency of Cameroon's macroeconomic and sociodemographic data is assessed by the IMF's General Data Dissemination System (GDDS). The coverage, periodicity, and timeliness for macroeconomic data in Cameroon are summarized in this study. The quality of the data, including their integrity and accessibility features, is assessed through an experimental data quality assessment framework that identifies six key aspects by which to judge the data. Economic data in Cameroon are also collected by statistical units in other government ministries, institutions, and civil registration offices.